Análisis de la compacidad urbana respecto a la morfología en un barrio de la Ciudad de Riobamba - Tacuri Quito, Trinidad Beatriz (2022)
The present study has the purpose of analyzing the urban compactness with regard to the morphology in a quarter of the city of Riobamba by means of criterion of sustainability regarding to the handling of dispersed cities, taking as a premise the current expansion of the city and the absence of information to determine the level of compactness that reaches this urban space. The investigation developed of form exploratory - analytical of the neighborhoods of the historical center that are provided with urban sustainable indicators (spaces of stay/ habitant) to determine the neighborhood object of study of which the level of compactness was analyzed and Ecology determined the grade of ecosystem balance by means of the comparison between opposing values and values established for sustainable cities as BCN. The values of compactness obtained in relation to the axis 1 of the sustainability for the neighborhood San Francisco are: insufficient with regard to the occupation of the soil, notable with regard to the public space and habitability and insufficient with regard to the mobility and services, reaching a grade C of ecosystem balance (being A the maximum and E the minimum).